Understanding the effect of transition metals and vacancy boron nitride catalysts on activity and selectivity for CO2 reduction reaction to valuable products: A DFT-D3 study. (1st July 2022) - Mudchimo, Tanabat; Takahashi, Kaito; Mano, Poobodin; Sanghiran Lee, Vannajan; Rungrotmongkol, Thanyada; Namuangruk, Supawadee
Highlights: The complete mechanism of CRR on various TM-DVBNs was investigated by DFT. TM dopings change the pathway, product selectivity, and activity of the catalyst. Ni-DVBN and Pd-DVBN produce CH3 OH, but other TM-DVBNs produce HCOOH and CH4. The ΔGOH, the universal descriptor, and ICOHP are activity indicators. Ni-DVBN is the most promising CRR catalyst with the highest activity and selectivity. Divacancy improves the CRR activity and selectivity compared to a single vacancy. Abstract: Single-atom catalysts have recently emerged as a promising approach for catalyzing the electrochemical CO2 reduction reaction (CRR). Transition metal (TM) atom doping to 2-dimensional layer material has been studied for CRR, but compared to studies on TM doped single vacancy (TM-SV) sites, those on double vacancies (TM-DV) sites are minor. In this research, we investigated the doping of 26 (3 d -, 4 d -, and 5 d -groups) TM atoms to the DV of boron nitride nanosheets (BN) using the dispersion-corrected density functional theory method for the complete CRR mechanism. We analyzed the limiting potential of the reactions of different TM-DVBN using the integrated crystal orbital Hamiltonian partition (ICOHP) of TM–O binding, universal descriptor, charge, and the number of valence electrons. We found the volcano plot model which suggests that a moderate OH binding energy of around −0.50 eV, the universal descriptor value around 9.40, and the ICOHP descriptor around −0.20 will provide the lowest limiting potential for CRR. From these studies, we find Ni-DVBN is the most reactive and can produce CH3 OH at −0.48 V. This is much better than Ni-SVBN, which requires −1.0 V to produce HCOOH also lower than Fe-SVBN (−0.52 V), which was the best catalyst in the previous study of TM-SVBN. This shows that Ni doping to DVBN is more effective for CRR compared to doping to SVBN.